Room-Temperature Synthesis of Ni and Pt-Co Alloy Nanoparticles Using a Microreactor - Watanabe, Satoshi; Koshiyama, Tomohiro; Watanabe, Takeshi; Miyahara, Minoru T. (Frontiers in Chemical Engineering, 2021)
Metal nanoparticles (NPs) are key materials used in a broad range of industries. Among the various synthetic routes of NPs, liquid-phase chemical reactions are promising because of their versatility in reaction conditions as well as their potential productivity. However, because the synthesis of NPs involves not only chemical reactions but also nucleation and growth processes, which are typically higher-order reactions in terms of the concentration, a small degree of nonuniformity in the concentration during mixing of reaction solutions can easily result in a wide size distribution of the resultant particles. A typical solution to this problem is to slow the rate of reactions compared with that of mixing; however, as a result, the synthetic processes often require long reaction periods and complex procedures. In this study, we applied a microreactor with excellent mixing performance to NP synthesis to simplify and intensify the processes. We synthesized nickel and platinum-cobalt alloy NPs as model materials. For the Ni NP synthesis, we demonstrated that the quick mixing provided by the microreactor enabled the precise control of the residence time, and consequently, monodispersed Ni NPs with an average size of 3.8 nm were synthesized. For the Pt-Co bimetallic system, the microreactor successfully produced Pt-Co alloy NPs, while batch-type synthesis with weaker mixing intensity resulted in a bimodal mixture of larger Pt NPs and smaller Co NPs. For both Ni and Pt-Co, monodispersed NPs were synthesized by simply mixing the reaction solutions in the microreactor at room temperature. These results demonstrate that the mixing process plays a key role in NP synthesis, and application of a microreactor enables the establishment of a facile and robust synthetic process.